HUBUNGAN PARITAS DENGAN DERAJAT LASERASI JALAN LAHIR DI POLINDES JETIS LOR KECAMATAN NAWANGAN KABUPATEN PACITAN - Etika Desi Yogi (Jurnal Delima Harapan, 2019)
For women, the perineum is very important stretching and lubricating the perineum during labor can weaken the pelvic floor muscles in the vaginal wall, trauma to the perineum also causes discomfort and pain during sexual intercourse and an estimated 85% of maternal mothers experience birth canal lacerations (Kettle and Tohil 2008). One of the fears that are often felt by pregnant women, especially third timers, is fear of being torn and afraid of sewing. Especially for mothers who have experienced it, this can make their own trauma when facing the birth process later (USU, 2006). The purpose of this study was to determine the relationship of parity to the degree of laceration of the birth pathway in Jetis Lor Polindes, Nawangan District, Pacitan Regency. The design or design in this study is correlation analysis, with the "retrospective" approach. This study analyzed the relationship of parity with the degree of laceration of the birth path in Jetis Lor Polindes, Nawangan District, Pacitan Regency. In this study, the population was all mothers giving birth at Jetis Lor Polindes, Nawangan District, Pacitan Regency. The samples in this study were all mothers giving birth at Jetis Lor Polindes, Nawangan District, Pacitan Regency. In this study by looking at the last 1 year data. In this study the independent variable is parity. In this study the dependent variable is the degree of laceration of the birth canal. Based on the calculation results of SPSS 11.5 for Windows, it was found that there was no relationship between parity and laceration degrees in the Jetis Lor Polindes, Nawangan Subdistrict, Pacitan Regency, from the results of probability (sig. 2-tailed) 0.22 <0.05.The researcher hopes that the mother will seek information and increase knowledge about the labor process, so that with good knowledge will reduce lacerations on the birth canal